What treatment outcomes in patients with endometrial cancer depend on? An existing knowledge and the new concepts - Sobotkowski, Janusz (Menopause Review/Przegląd Menopauzalny, 2009)
Efficacy of fight against endometrial cancer depends on proper kind and method choice of treatment of patient. Individual treatment planning has a crucial importance for outcomes of therapy and is based on performance status evaluation, stage of cancer, its morphological form and on diagnostic and therapeutic potential of treating center. Scientific and basic investigations on biological, molecular and genetic features on cancer cells may lead to 5-years survival improvement. Common, traditional knowledge on prognostic factors author reviewed and new trends in research on endometrial cancer cells discussed.